2008
DOI: 10.1007/s12149-007-0120-1
|View full text |Cite
|
Sign up to set email alerts
|

Generation of planar images from lung ventilation/perfusion SPECT

Abstract: The reprojected planar images provide high-count, high-quality images, which are comparable with conventional 2D images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Comparisons of reprojected images with standard planar V/Q scans showed similar detail and distribution of radiopharmaceuticals (39). It was believed that reprojected images could replace true planar images with no loss of diagnostic sensitivity (39). Subsequent comparisons showed that reprojected reconstructions resulted in more matched defects but no differences in interpretation from true planar V/Q scans (40).…”
Section: Technical Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…Comparisons of reprojected images with standard planar V/Q scans showed similar detail and distribution of radiopharmaceuticals (39). It was believed that reprojected images could replace true planar images with no loss of diagnostic sensitivity (39). Subsequent comparisons showed that reprojected reconstructions resulted in more matched defects but no differences in interpretation from true planar V/Q scans (40).…”
Section: Technical Studiesmentioning
confidence: 95%
“…Two methods for producing planarlike V/Q scans from SPECT V/Q scans have been described: the angular summed method (22,23) and reprojected scans (39). Comparisons of reprojected images with standard planar V/Q scans showed similar detail and distribution of radiopharmaceuticals (39). It was believed that reprojected images could replace true planar images with no loss of diagnostic sensitivity (39).…”
Section: Technical Studiesmentioning
confidence: 99%
“…Although Bailey et al have described a technique using reprojection (28), many of the commercial vendors offer a simpler approach using an angular summing technique (14). With this approach, images are generated by summing several consecutive projections from the SPECT acquisition.…”
Section: V/q Spect Techniquementioning
confidence: 99%
“…Reprojected planar images were constructed at a later time, at the same views as the traditional planars, using the reprojection algorithm supplied with the processing software (Hybrid Recon Lung, v1.0.15). The basis of this method has been described elsewhere [10]. In short, the scatter window was used to generate the outline of the patient body and the photopeak was used to outline the lungs.…”
Section: Scintigraphic Imagingmentioning
confidence: 99%